If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1.7t = t Solving 3 + -1.7t = t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 3 + -1.7t + -1t = t + -1t Combine like terms: -1.7t + -1t = -2.7t 3 + -2.7t = t + -1t Combine like terms: t + -1t = 0 3 + -2.7t = 0 Add '-3' to each side of the equation. 3 + -3 + -2.7t = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2.7t = 0 + -3 -2.7t = 0 + -3 Combine like terms: 0 + -3 = -3 -2.7t = -3 Divide each side by '-2.7'. t = 1.111111111 Simplifying t = 1.111111111
| 10(x+3)=x-5+3 | | 5x-2+3x=16-2x | | -40x+5=-50x | | a^2-5ag-50g^2=0 | | 2.5+x=31 | | 2-3(a+5)=-16 | | 12y+4x=3 | | -16x^2+28x+25=0 | | h=-16t^2+100t+3 | | (3x^2)-x+9=0 | | 6v-8=34 | | .31(x+8)=-19 | | 5(2c+d)6(c+2d)= | | -16x^2+28+25=0 | | -50.00+1.00x=0.80(x-100.00) | | 8x^2-3x+32=0 | | 7=3x-5-7-7 | | 0.10+10=0.35x | | 6+y=2x | | 3=-1t | | 12y-4x=3 | | 0.10+10=0.35 | | 8x+12y=1580 | | 4x-1+12x-17= | | 9-3b+6b= | | (X-4)=-8 | | 11p+7p+4p=27 | | Cscx-secx=0 | | 4x^2=20x-28 | | Y=3x(2x-1)(x+3) | | .10(x+7)=30 | | 18=2g |